Efficacy of micafungin for the treatment of invasive candidiasis and candidaemia in patients with neutropenia. Issue 5 (2nd February 2018) - Chandrasekar, Pranatharthi; Sirohi, Bhawna; Seibel, Nita L.; Hsu, Jack W.; Azie, Nkechi; Wu, Chunzhang; Ruhnke, Markus
Summary: Neutropenia is linked to the development of invasive candidiasis/candidaemia, for which micafungin has demonstrated efficacy, but evidence in patients with neutropenia is limited. The aim of this study was to evaluate the efficacy of micafungin for the treatment of invasive candidiasis/candidaemia in patients with neutropenia (<500 neutrophils/μL) and without neutropenia. This pooled, post hoc analysis of 2 Phase 3 trials compared micafungin 100 mg/d (adults) and 2 mg/kg/d (paediatrics) with L‐AmB 3 mg/kg/d (NCT00106288) and micafungin 100 mg/d and 150 mg/d with caspofungin 70 mg/d followed by 50 mg/d (adults) (NCT00105144); treatment duration 2‐4 weeks (≤8 weeks for chronic disseminated candidiasis). Effects of neutropenia duration and Candida spp. on efficacy outcomes (treatment success, clinical and mycological response) were examined. Of 685 patients, 77 had neutropenia. The most common infection in patients with/without neutropenia was due to C. tropicalis (31/77) and C. albicans (295/608) respectively. Overall success was numerically lower in patients with vs without neutropenia (63.6% vs 72.9%). Clinical and mycological response was similar between groups. Neutropenia duration or Candida spp. did not impact micafungin's overall success rate. This analysis supports evidence that micafungin is effective against invasive candidiasis/candidaemia in patients with neutropenia, irrespective of neutropenia duration or Candida spp., although overall success may be lower than in patients without neutropenia.